2018
DOI: 10.1016/j.foodres.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale structural changes of starch and proteins during pea flour extrusion

Abstract: Dehulled yellow pea flour (48.2% starch, 23.4% proteins, d.b.), was processed by a twin-screw extruder at various moisture contents MC (18-35% w.b.), product temperature T (115-165 °C), and specific mechanical energy SME (50-1200 kJ/kg). Structural changes of extruded pea flour were determined at different scales by measurements of density (expansion), crystallinity (X-ray diffraction), gelatinisation enthalpy (DSC), starch solubility in water and protein solubility in SDS and DTE (SE-HPLC). Foam density dropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 39 publications
5
50
0
Order By: Relevance
“…However, the a values of the extrudates were higher than those of the formula flour. Similar results were obtained by Kristiawan et al [31] in the extrusion of pea flour. It can be concluded that some components of the blends changed during the extrusion process.…”
Section: Effect Of Extrusion Parameters On the Sensory Properties Of supporting
confidence: 91%
See 1 more Smart Citation
“…However, the a values of the extrudates were higher than those of the formula flour. Similar results were obtained by Kristiawan et al [31] in the extrusion of pea flour. It can be concluded that some components of the blends changed during the extrusion process.…”
Section: Effect Of Extrusion Parameters On the Sensory Properties Of supporting
confidence: 91%
“…It can be concluded that some components of the blends changed during the extrusion process. Kristiawan et al [31] also found that L and a were correlated with protein aggregations by covalent bonds in the samples.…”
Section: Effect Of Extrusion Parameters On the Sensory Properties Of mentioning
confidence: 90%
“…Dehulled yellow pea (Ohtsuya Inc., Tokyo, Japan), unshelled pea (Toyota Tsusho Foods Corp., Tokyo, Japan), chickpea (Bob's Red Mill Inc., Milwaukee, OR, USA), and lentil (Beans Market Inc., Shizuoka, Japan) sold in Japan for food use were purchased. We then used these legume flours to prepare noodles using extrusion molds [16]. Briefly, 50% water was added to the legume flour, kneaded, extruded at 120 • C, and then air dried.…”
Section: Test Materialsmentioning
confidence: 99%
“…The increase in phenolic content with barrel temperature has been ascribed to the formation of Maillard reaction products [42]. The effect of extrusion on bioactive compounds depends on the physical and chemical characteristics of the product and the extrusion conditions [43,44].…”
Section: Total Phenolic Contentmentioning
confidence: 99%